The forts and castles of Ghana: a collective monument (Bulletin KNOB, 1989)
In the colonial history or the history of European expansion like one prefers to call her nowadays the trade forts which have been built in the course of times on Africa's west coast and especially on the Gold coast, play an important role. Ten years before Columbus discovered America the castle Sao Jorge da Mina was built by the Portuguese on a spit of land in Elmina, which already for some time was an important market where merchants from the deep interior exchanged gold and draperies from the Mediterranean area against salt and smoked fish.Soon it appeared that these African merchants coming with their goods along the caravan routes through the Sahara to Elmina could not compete with the Portuguese. They had to make way for the 'Akannists' who exchanged gold, ivory and other wood products for Portuguese goods. To be able to draw off the gold stream even better the Portuguese still built two or three other fortified trade posts and till ca. 1600 they could monopolize that trade.However that changed when the Dutch built a little fort in Mori on a special request of the local sovereign whose subjects regularly were exposed to reprisals of the Portuguese because of their 'illegal' trade with the Dutch. With this the first step had been done for the proliferation of trade forts on the Gold coast. Soon a sort of international gold-rush was developed and before the 17th century was over Dutch, Englishmen, Danes, Swedes, Brandenburgers and French had built more than thirty fortified trade posts on a coastal strip less than 300 km long.Each fort formed the terminus of one of the ramifications of the main trade routes from the interior. The sharpest trade practices were used at the competition with the European neighbour, who sometimes had lodged himself within range of an already existing fort. This way a sort of West-African ‘shopping street’ of forts and castles came into existence, where during many centuries African and European merchants bartered with each other on a footing of equality. The Europeans only were hirers of the soil their forts stood on and had no power outside the walls of their establishments. That one also dealt in slaves next to gold and ivory does not alter this fact. About twenty of these buildings are left, some in a ruinous, others in a reasonably well condition. Some are beautifully situated, others are less interesting. But as a whole they form a collective monument of a piece of world history wherein three continents were involved at the same time, the famous triangular trade which left behind a deep track of wealth and perdition.